Leakage resilient CCA secure IBE with all-but-one lossy filter. (2016) - Wang, Zhiwei
The goal of this paper is to design an id-based encryption (IBE) scheme that can flexibly tolerate leakage bounds, by only increasing the size of secret key proportionally, and the security level can be achieved to be against chosen-ciphertext attacks (CCA). As our main technical tool for CCA security, we introduce an initiation of all-but-one lossy filter, which is a simple version of all-but-many lossy filter to the leakage resilient settings. As our main result, we use the all-but-one lossy filter to construct an IBE scheme that is secure against leakage resilient chosen-ciphertext attacks (CCA), and the leakage rate is 1/2 − ο(1).